High production of ectoine from methane in genetically engineered Methylomicrobium alcaliphilum 20Z by preventing ectoine degradation - Sang Eun Lim; Sukhyeong Cho; Yejin Choi; Jeong-Geol Na; Jinwon Lee (Microbial Cell Factories, 2024)
Abstract Background Methane is a greenhouse gas with a significant potential to contribute to global warming. The biological conversion of methane to ectoine using methanotrophs represents an environmentally and economically beneficial technology, combining the reduction of methane that would otherwise be combusted and released into the atmosphere with the production of value-added products. Results In this study, high ectoine production was achieved using genetically engineered Methylomicrobium alcaliphilum 20Z, a methanotrophic ectoine-producing bacterium, by knocking out doeA, which encodes a putative ectoine hydrolase, resulting in complete inhibition of ectoine degradation. Ectoine was confirmed to be degraded by doeA to N-α-acetyl-L-2,4-diaminobutyrate under nitrogen depletion conditions. Optimal copper and nitrogen concentrations enhanced biomass and ectoine production, respectively. Under optimal fed-batch fermentation conditions, ectoine production proportionate with biomass production was achieved, resulting in 1.0 g/L of ectoine with 16 g/L of biomass. Upon applying a hyperosmotic shock after high–cell–density culture, 1.5 g/L of ectoine was obtained without further cell growth from methane. Conclusions This study suggests the optimization of a method for the high production of ectoine from methane by preventing ectoine degradation. To our knowledge, the final titer of ectoine obtained by M. alcaliphilum 20ZDP3 was the highest in the ectoine production from methane to date. This is the first study to propose ectoine production from methane applying high cell density culture by preventing ectoine degradation.